Effect of fermented Jatropha curcas meal combined with enzymes on metabolizable energy, retention of N, P, Ca and digesteble crude fiber - Yenni Yusriani; T. Toharmat; Sumiati .; E. Wina; A. Setiyono (Indonesian Center for Animal Research and Development (ICARD), 2011)
Jatropha curcas meal (JCM) contain high protein, but its utilization as feed ingredient is limited by the presence of several anti nutritive and toxic compounds. A research has been conducted in the Faculty of Animal Husbandry IPB to determine the values of metabolizable energy, crude fiber digestibility, retention of nitrogen, calcium and phosphorous of JCM fermented using Rhizopus oligoporus or of fermented JCM suplemented with enzymes on chickens. In this experiment 25 of ten weeks old chickens were used (20 chickens were fed experimental diets, and 5 chickens were used to measure endogenous energy). A Completely Randomized Design (CRD) with 5 treatments and 4 replications was used in this experiment. The experimental diets were R0 = basal diet without JCM; R1 = the diet contained unprocess JCM 5%; R2 = the diet contained fermented JCM 5%+ cellulase 20.000 U/kg; R3 = the diet contained 5% of fermented JCM + phytase 1000 FTU/kg; R4 = the diet contained 5% of fermented JCM+ cellulase 20.000 U/kg + phytase 1000 FTU/kg. The parameters measured were Metabolizable Energy (ME, Men, TME, TMEn) digestibility of crude fiber and retention of calcium, phosphorus and nitrogen. The result indicated that fermented JCM suplemented enzym phytase, cellulase as well as enzym combination increased metabolizable energy. Nitrogen retention was improved highest significantly (P < 0.01) by feed of fermented JCM suplemented enzyme compared to control diet or diet containing untreated JCM. The fermented JCM suplemented with phytase enzyme (R3) gave the highest nitrogen retention (76.73%.). The highest value of digested crude fibre (24.65%) was on the diet containing fermented JCM suplemented with cellulase (R2). The calcium retention improved significantly (P < 0.05) with diet containing fermented JCM supplemented enzyme compared to that of the diet containing untreated JCM. It can be concluded that fermented JCM supplemented enzymes cellulase, phytase and its combination increased the value of metabolizable energy, digestibility of crude fiber and nitrogen retention. Key Words: Chicken, JCM Fermented, Enzymes, Metabolic Energy